Evaluación antimicótica de extracto y aceite esencial de Pumamaqui (Oreopanax ecuadorensis Seeman.) frente a: Trichophyton mentagrophytes ATCC 9533, Trichophyton rubrum ATCC 28188, Microsporum canis ATCC 36299, Candida albicans ATCC 10231, Patógenos de Dermatomicosis. - Carrillo Murillo, Carlos Alberto (2016)
Ecuador is considered to be one of the mega diverse countries on a global scale, this plenty of natural wealth, unfortunately it is slightly well-known, inclusive for the same Ecuadorians, a big percentage of these plants has not been studied up to the actuality, leaving an almost intact field for diverse investigations. In this project we worked with the species Pumamaqui (Oreopanax ecuadorensis Seeman.) Endemic to the Andean region of Ecuador and is known for its disinfectant to clean wounds dermatitis. The target of this investigation was to evaluate the antifungal activity of the species Pumamaqui (Oreopanax ecuadorensis Seeman.), on pathogenic fungi, responsible for the dermatomicosis. One worked with two types of extracts: fluid and soft, which were extracted from the humectation and percolation with alcohol to 96 % of purity, as well as of essential oil extracted by means of the distillation for steam dragging, to different concentrations. For the determination of the antifungal activity there were used the methods of Kirby-Bauer and Barry's method. The statistical treatment given to the results was the analysis of variance ANOVA one-way, with a confidence level of 95% with which it can be concluded that the effectiveness of both the essential oil and the soft extract is 75% and for the fluid extract is only 25% against pathogenic fungi that cause the dermatomicosis.